2009
DOI: 10.1002/sia.3121
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam irradiation: morphological and chemical evolution in epoxy polymers

Abstract: This work contributes to the understanding of focused ion beam (FIB) technology for polymers. The conditions of treatment are varied, in particular by etching under 'dry' ultra-high vacuum conditions or in the presence of water vapour. For a glassy epoxy network, the changes in chemistry and morphology are characterised. Energy-dispersive X-ray analysis reveals that gallium is always implanted in the epoxy but the content is higher in the case of 'dry' FIB milling. According to attenuated total reflection infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Poly(styrene) therefore tends to cross‐link after exposure to radiation. It has been shown that the introduction of water vapor during Ga + ion bombardment of PS maintains a high sputtering rate, presumably due to the reaction of water with radical species and the prevention of cross‐linking …”
Section: Resultsmentioning
confidence: 99%
“…Poly(styrene) therefore tends to cross‐link after exposure to radiation. It has been shown that the introduction of water vapor during Ga + ion bombardment of PS maintains a high sputtering rate, presumably due to the reaction of water with radical species and the prevention of cross‐linking …”
Section: Resultsmentioning
confidence: 99%
“…Possible routes to minimize the damage caused by the ion beam include milling the polymers at cryogenic temperatures (e.g. −150°C) to reduce local heating (Niihara et al ., 2005; Sezen et al ., 2009; Kim et al ., 2011; Sezen et al ., 2011), applying an electrically conductive coating or using an electron flood gun against ion charging (Stokes et al ., 2007) or removing the polymer at a faster rate using water vapour (Kochumalayil et al ., 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…While the utility of FIB nanomachining and ISE imaging was demonstrated for two specific bicomponent polymer systems, harnessing the full potential of nanomachining and differential sputtering to reveal morphology hinges on the ability to optimize FIB sputtering conditions for different polymeric systems. Sputtering of polymers is likely a complex process dependent on both the polymer's properties and FIB beam parameters [2,3]. Of all the polymer properties, crystallinity influences many of the polymer mechanical properties such as hardness.…”
mentioning
confidence: 99%